Sports training in virtual reality with a focus on visual perception: A systematic review - Witte, K.; Bürger, D.; Pastel, S. (Frontiers in Sports and Active Living, 2025)
Introduction: There is an increasing endeavor to use Virtual Reality (VR) technologies in sports training. Because visual perception is crucial for sports performance, it should also be considered in the development of VR tools. The aim of this review is to summarise the literature on the application fields and domains of sport in VR and to examine what needs to be considered when developing such VR training tools with regard to visual perception and its manipulation. Furthermore, it is still unclear to what extent the user's body or that of their teammates or opponents must be visualized in VR.